New species and new records of dendrochirotid and dactylochirotid holothuroids (Echinodermata : Holothuroidea) from off the east coast of South Africa - Thandar, Ahmed S. (Zootaxa, 2006)
Numerous unidentified specimens of Holothuroidea received from the Natal and South African Museums or present in the collections of the former University of Durban-Westville, contain several new species and many that are new to the fauna of South Africa. This paper includes descriptions of new species or new records of several dendrochirotid holothuroids and a dactylochirotid from off the east coast of South Africa, extending from Kosi Bay in the north to the Port St Johns-East London area, in the Eastern Cape Province, the latter region represents the transition zone between the southern African subtropical and warm-temperate zoogeographical provinces. A few other species have been added if they represent juvenile material, or considered extensions of ranges (bathymetric or otherwise) of previously known species, or confirmation of a species previously recorded from a single locality in the region under consideration. Of the 16 species here treated, four are new to science, seven new to the fauna of South Africa, whereas the rest are either extension of ranges or additional records. The four new species are Psolidium multipes, P. acorbula, Ekkentropelma groovia and Psolidothuria yasmeena. The following six species are additions to the fauna of South Africa: Thyone avenusta Cherbonnier, 1970; T. comata Cherbonnier, 1988; Selenkiella paradoxa Cherbonnier, 1970; Ohshimella ocula (Cherbonnier, 1988); Plesiocolochirus tessellarus (Cherbonnier, 1970) and Staurothyone rosacea (Semper, 1869). Pseudocolochirus dispar (Lampert, 1889) is new to the fauna of southern Africa, recorded for the first time from Mozambique. The remaining species include Stolus pseudoalbescens Thandar, 2005; Sclerothyone velligera (Ludwig & Heding, 1935); Ohshimella ehrenbergii (Selenka, 1868); Pawsonellus africanus Thandar, 1986 and Trachasina crucifera (Semper, 1869).